Esophageal Histological Precursor Lesions and Subsequent 8.5-Year Cancer Risk in a Population-Based Prospective Study in China - Wei, Wen-Qiang; Hao, Chang-Qing; Guan, Chen-Tao; Song, Guo-Hui; Wang, Meng; Zhao, De-Li; Li, Bian-Yun; Bai, Wen-Long; Hou, Pei-Yong; Wang, Jin-Wu; Jin, Guo-Liang; Lei, Fu-Hua; et al. (The American journal of gastroenterology, 2020)
Data on the associations between esophageal histological lesions and risk of esophageal squamous cell carcinoma (ESCC) in general populations are limited. We aimed to investigate these associations in a large Chinese general population to inform future Chinese ESCC screening guidelines. We performed endoscopic screening of 21,111 participants aged 40-69 years from 3 high-risk areas of China in 2005-2009, and followed the cohort through 2016. Cumulative incidence and mortality rates of ESCC were calculated by baseline histological diagnosis, and hazard ratios of ESCC, overall and by age and sex, were assessed using the Cox proportional hazards models. We identified 143 new ESCC cases (0.68%) and 62 ESCC deaths (0.29%) during a median follow-up of 8.5 years. Increasing grades of squamous dysplasia were associated with the increasing risk of ESCC incidence and mortality. The cumulative ESCC incidence rates for severe dysplasia/carcinoma in situ, moderate dysplasia (MD), and mild dysplasia were 15.5%, 4.5%, and 1.4%, respectively. Older individuals (50-69 years) had 3.1 times higher ESCC incidence than younger individuals (40-49 years), and men had 2.4 times higher ESCC incidence than women. This study confirmed that increasing grades of squamous dysplasia are associated with increasing risk of ESCC and that severe dysplasia and carcinoma in situ require clinical treatment. This study suggests that in high-risk areas of China, patients with endoscopically worrisome MD should also receive therapy, the first screening can be postponed to 50 years, and endoscopic surveillance intervals for unremarkable MD and mild dysplasia can be lengthened to 3 and 5 years, respectively.